Efektivitas layanan informasi terhadap pemahaman masa pubertas siswa - Cusiyah Cusiyah; Sri Utami; Lusiana Wulansari (Universitas Indraprasta PGRI, 2022)
this study aims to determine whether information services are effective in increasing students' understanding of puberty. This study uses a quantitative approach with a pre-experimental one group pretest-posttest method. The population in this study were 84 students of class VII. The sample was drawn purposively with a size of 12 students. Data were collected using a questionnaire on understanding of puberty, which amounted to 33 items. The data were analyzed descriptively to determine the norm of categorization of variables. The hypothesis was tested using t test. The results of the study revealed that information services were effective in increasing students' understanding of puberty.